KOMUNIKASI PENYULUHAN DINAS TANAMAN PANGAN DAN HOLTIKULTURA DALAM MENINGKATKAN PRODUKSI PADI DI KECAMATAN SABAK AUH KABUPATEN SIAK - ", Eswandi; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study analyzes How the Food Crops Extension Communications And Holtikulkultura to Increase Rice Production In District Sabak Auh Siak. Given that and see rice production in the district of Sabak Auh decreased 10.010 tons, 8,295 tons to 6,900 tons / year 2015. These numbers show that the rate of production of paddy in the district of Sabak Auh declining and needs to be returned. how communication outreach should be a step and an important role in agricultural programs. The purpose of this study was to determine how communication education, communication methods counseling, and factors inhibiting Communications Extension Department of Food Crops and Horticulture to Increase Rice Production In District Sabak Auh Siak. To analyze this problem researchers use diffusion of innovation theory in accordance with these problems, namely how communication education, communication methods, factors inhibiting agricultural extension communication. The research was conducted at the Food Crops and Horticulture Siak, using qualitative research method descriptive his presentation by purposive sampling technique. In collecting the data the researcher used interview, observation and documentation. Based on informants principal investigator resources in seeing how the communication of extension of Food Crops and Horticulture, communication methods, and also an inhibiting factor this extension communication among other factors communications, human resources. Keywords : Communication Process, Communication Methods, inhibiting factors komunkasi counseling.